The Fujifilm X-E2 : beyond the manual - Pfirstinger, Rico (Rocky Nook : Distributed by O'Reilly Media, 2014)
The Fujifilm X-E2: Beyond the Manual provides experience-based information and insights for owners of the Fujifilm X-E2 mirrorless system camera. Fuji X-Pert series author Rico Pfirstinger teaches little-known capabilities of the X-E2 that he's discovered through several months of in-depth research. This book focuses on insights that you won't find in the manual, skipping tedious explanations of basic camera functions and operations. Instead, it cuts to the chase and provides readers with a plethora of tips and practical instructions that will enable them to fully explore the capabilities of.